2018
DOI: 10.1016/j.coviro.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses in influenza A virus and human coronavirus infections: an ongoing battle between the virus and host

Abstract: Respiratory viruses, especially influenza A viruses and coronaviruses such as MERS-CoV, represent continuing global threats to human health. Despite significant advances, much needs to be learned. Recent studies in virology and immunology have improved our understanding of the role of the immune system in protection and in the pathogenesis of these infections and of co-evolution of viruses and their hosts. These findings, together with sophisticated molecular structure analyses, omics tools and computer-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 149 publications
(193 reference statements)
4
54
0
1
Order By: Relevance
“…It has also been found that the Spike protein of SARS-CoV-2 has a stronger binding to ACE2 receptor than its SARS-CoV parallel. This is indicative of the evolution of this viral family to undergo enhanced adaptation with the human genome and could be speculated as a case of co-evolution (Zheng and Perlman, 2018). At this point, summoning the hypothesis strongly held in this study it could be speculated that proteins of the SARS-CoV-2 will evolve more divergently with perhaps enhanced affinity towards human cell substrates.…”
Section: Sars-cov-2-nsp15 (Endoribonuclease)supporting
confidence: 62%
“…It has also been found that the Spike protein of SARS-CoV-2 has a stronger binding to ACE2 receptor than its SARS-CoV parallel. This is indicative of the evolution of this viral family to undergo enhanced adaptation with the human genome and could be speculated as a case of co-evolution (Zheng and Perlman, 2018). At this point, summoning the hypothesis strongly held in this study it could be speculated that proteins of the SARS-CoV-2 will evolve more divergently with perhaps enhanced affinity towards human cell substrates.…”
Section: Sars-cov-2-nsp15 (Endoribonuclease)supporting
confidence: 62%
“…During a viral infection, host pathogen-recognition receptors (PRRs) initially sensitized by viral pathogen-associated molecular patterns and cascades of signaling pathways are activated to produce type 1 interferons (IFNs). IFNs are the prominent cytokines in innate immune response, and are thought to enhance the release of antiviral proteins for the protection of uninfected cells [5,63]. CoV can be sensed by three types of PRR, including Toll-like receptors, retinoic acid-inducible gene I (RIG-I)-like receptors, and nucleotide-binding and oligomerization domain (NOD)-like receptors [4].…”
Section: Discussionmentioning
confidence: 99%
“…In SARS, macrophages and dendritic cells are only abortively infected and natural killer cells are not activated by the virus, thus suggesting a defective innate immune response with an altered virus clearance [6]. In a mouse model using the related coronavirus, delayed type-I IFN responses (with IFN levels peaking later in the immune response and remaining elevated) were associated with mortality from severe lung disease, due to recruitment of highly inflammatory macrophages into the lung [16,17]. Studies of human SARS-CoV infections also strongly suggest that dysregulated and persistently elevated type-I IFN responses are associated with severe human lung disease [18].…”
Section: Anti-rheumatic Drugs As Possible Therapies: Antimalarials Amentioning
confidence: 99%
“…They may have a decreased IFN response to the virus, which would cause excess virus replication, but they also might have less risk of severe lung disease due to downregulation of the IFN signaling pathway. This illustrates the difficult balance between an adequate immune response to prevent viral replication and an over-exuberant immune response that causes severe lung pathology [17]. The role of type I IFN in SARS-CoV2 and the role of blocking IFN-I pathways therefore requires more detailed studies.…”
Section: Anti-rheumatic Drugs As Possible Therapies: Antimalarials Amentioning
confidence: 99%